(untitled) (SCIENCE TIME JOURNAL, 2025)
this study investigates the effectiveness of the ‘Visualization’ method in developing oral communication and auditory comprehension skills of visually impaired students in grades 8–10. Using a mixed-method approach, the research evaluates improvements in language performance, engagement, and self-expression. Findings demonstrate that visualization-based strategies enhance linguistic interaction, listening comprehension, and speaking fluency, providing an adaptable framework for inclusive language education